DRAK2 Participates in a Negative Feedback Loop to Control TGF-β/Smads Signaling by Binding to Type I TGF-β Receptor - Kyung-Min Yang; Wonjoo Kim; Eunjin Bae; Jungsoo Gim; Brian M. Weist; Yunshin Jung; Ja-Shil Hyun; Jennifer B. Hernandez; Sun-Hee Leem; Taesung Park; Joon Jeong; Craig M. Walsh; et al. (Cell Reports, 2012)
TGF-β1 is a multifunctional cytokine that mediates diverse biological processes. However, the mechanisms by which the intracellular signals of TGF-β1 are terminated are not well understood. Here, we demonstrate that DRAK2 serves as a TGF-β1-inducible antagonist of TGF-β signaling. TGF-β1 stimulation rapidly induces DRAK2 expression and enhances endogenous interaction of the type I TGF-β receptor with DRAK2, thereby blocking R-Smads recruitment. Depletion of DRAK2 expression markedly augmented the intensity and the extent of TGF-β1 responses. Furthermore, a high level of DRAK2 expression was observed in basal-like and HER2-enriched breast tumors and cell lines, and depletion of DRAK2 expression suppressed the tumorigenic ability of breast cancer cells. Thus, these studies define a function for DRAK2 as an intrinsic intracellular antagonist participating in the negative feedback loop to control TGF-β1 responses, and aberrant expression of DRAK2 increases tumorigenic potential, in part, through the inhibition of TGF-β1 tumor suppressor activity.